The metabolic pathways and environmental controls of hydrocarbon biodegradation in marine ecosystems - Andreas P. Teske; Samantha B. Joye; Joel E. Kostka; Ian Head (Frontiers Media SA, 2015)
Biodegradation mediated by indigenous microbial communities is the ultimate fate of the majority of oil hydrocarbon that enters the marine environment. The aim of this Research Topic is to highlight recent advances in our knowledge of the pathways and controls of microbially-catalyzed hydrocarbon degradation in marine ecosystems, with emphasis on the response of microbial communities to the Deepwater Horizon oil spill in the Gulf of Mexico. In this Research Topic, we encouraged original research and reviews on the ecology of hydrocarbon-degrading bacteria, the rates and mechanisms of biodegradation, and the bioremediation of discharged oil under situ as well as near in situ conditions.
English
Keywords: Biodegradation; Metagenomics; oil spill; metatran; bacterioplankton; Bacteria; Gulf of Mexico; microbial communities; hydrocarbon; Deepwater Horizon